Nomenclature and clinical phenotypes of atopic dermatitis - Giampiero Girolomoni; Marjolein de Bruin-Weller; Valeria Aoki; Kenji Kabashima; Mette Deleuran; Luis Puig; Ashish Bansal; Ana B. Rossi (SAGE Publishing, 2021)
Atopic dermatitis is a heterogeneous disease and resists classification. In this review, we discuss atopic dermatitis nomenclature and identify morphologic phenotypes, which will facilitate correct diagnoses and development of treatment strategies. We support using the term 'atopic dermatitis' rather than eczema, because it describes the allergic background and inflammation ('itis') as drivers of the disease. Atopic dermatitis has many morphologic manifestations that vary by topographic area affected, age, or race and require consideration in differential diagnosis. Different phenotypes based on morphology and topographic location, ethnicity, and age are discussed. A better-defined phenotype identification for atopic dermatitis will facilitate earlier and correct diagnosis of this complex condition and inform selection of the most appropriate treatment choice in an era in which targeted therapies may generate more individualized patient care.